Meiotic nuclear movements in fission yeast are regulated by the transcription factor Mei4 downstream of a Cds1-dependent replication checkpoint pathway - Ruan, Kun (Genes Cells, 2015)
In meiosis, the fission yeast nucleus displays an elongated morphology, moving back and forth within the cell; these nuclear movements continue for approximately 2 h before meiotic nuclear divisions. Meiotic DNA replication occurs in an early phase of the nuclear movements and is followed by meiotic prophase. Here we report that in mutants deficient in meiotic DNA replication, the duration of nuclear movements is strikingly prolonged to four to 5 h. We found that this prolongation was caused by the Cds1-dependent replication checkpoint, which represses expression of the mei4(+) gene encoding a meiosis-specific transcription factor. In the absence of Mei4, nuclear movements persisted for more than 8 h. In contrast, overproduction of Mei4 accelerated termination of nuclear movements to approximately 30 min. These results show that Mei4 is involved in the termination of nuclear movements and that Mei4-mediated regulatory pathways link a DNA replication checkpoint to the termination of nuclear movements.